WebXR Asset Management in Developing Virtual Reality Learning Media - Matahari, Tombak (Faculty of Engineering and Technology, Sampoerna University, 2022)
Extended Reality (XR) is the technology that allows blending virtual and physical worlds using augmented reality (AR) and Virtual Reality (VR) to create a fully immersive experience. While WebXR is a web based XR environment built on a JavaScript framework that enables interactivity of AR and VR devices within the web browser. Contemporarily, educators are demanded to explore the variety of new media in practicing interactive learning, specifically in an academic environment. Arguably, VR has recently been identified as one of the most popular gamification mediums. It can create an environment that is both physically and digitally engaging. This paper reviews, simplifies as well as recommends a better component management system in the VR production pipeline using practice-based research methodology.